The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1111/jpy.12507
|View full text |Cite
|
Sign up to set email alerts
|

Differential toxic effects of Ulva lactuca (Chlorophyta) on the herbivorous gastropods, Littorina littorea and L. obtusata (Mollusca)

Abstract: Members of the genus Ulva are widespread and abundant in intertidal and shallow subtidal areas but there are conflicting data regarding susceptibility to herbivory. While some studies have documented that Ulva spp. were favored by a diversity of marine herbivores, other work has revealed herbivore deterrence. We investigated grazing and growth rates of the littorinid species, Littorina littorea and L. obtusata, when offered Fucus vesiculosus, Ascophyllum nodosum, Ulva lactuca, and Chondrus crispus, highlightin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 77 publications
(147 reference statements)
1
8
0
1
Order By: Relevance
“…obtusata (Peckol & Putnam, 2017). The present study shows the potential of A. armata Regarding effects on G. umbilicalis, A. armata induced a significant increase in total lipids, along with decreased activities of LDH and ETS.…”
Section: Discussionmentioning
confidence: 99%
“…obtusata (Peckol & Putnam, 2017). The present study shows the potential of A. armata Regarding effects on G. umbilicalis, A. armata induced a significant increase in total lipids, along with decreased activities of LDH and ETS.…”
Section: Discussionmentioning
confidence: 99%
“…While green macroalgae have been traditionally thought of as non-toxic, increasing evidence has shown that species of ulvoid macroalgae can inhibit co-occurring phytoplankton (Nan et al 2008;Tang & Gobler 2011), macroalgae (Gao et al 2014), and invertebrates (Nelson & Gregg 2013, Van Alstyne et al 2014, Peckol & Putnam 2017.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, all of the CYP2 transcripts were more highly expressed in I. balthica fed with U. lactuca than in isopods fed with F. vesiculosus . Several recent studies have shown that Ulva produces a range of secondary metabolites which deter both gastropods 18 and sea urchins 39 . F. vesiculosus also possesses a range of secondary metabolites, but as F. vesiculosus is the natural diet of I. balthica , we can speculate that they might be able to detoxify F. vesiculosus compounds through a separate, taxon-specific, pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In common periwinkles ( Littorina spp. ), a recent study found that the deterrence effects of Ulva lactuca were species-specific, which the authors hypothesized could be due to differences in feeding strategies (generalist vs specialist) 18 .…”
Section: Introductionmentioning
confidence: 99%